Factors affecting delegation authority toward employees performance - Alhosani, Adnan; Md Yusoff, Rosman; Ismail, Fadillah; Ur Rehman, Fazal (Penerbit UTHM, 2018)
Employees are the key asset of every organization and their performance can influence the goals and objectives of organizations in a positive or negative way. The aim of this study is to develop a theoretical framework in relations to examine the effects of employee’s satisfaction and participation, delegation authority and empowerment on employee’s performance in UAE organizations. Specifically, to get an in-depth understanding of the linkage between delegation authority and employees performance with emphasize on (employee participation and employee satisfaction). This study is only limited to Dubai organizations and future research may be conducted in other countries as well as can assess the moderating role in the defined variables. By integrating employee’s satisfaction and participation, delegation authority and empowerment, and employee’s performance literature, the main contribution of this paper is the analysis of defined variables in Dubai organizations with emphasize on new challenges and to boost up the gap of relevant literature.